The Effect of Liquidity Ratios, Solvency and Activities on Financial results as measured by ROE in Manufacturing Companies in the Food and Beverage Subsector listed on the IDX for the 2017-2019 Period - Silvi Meliani; Yulia Nurfitriani Harnaen; Zaldi Saputra; Fitri Mareta; Elin Paulina (Future Science, 2020)
The goal of this study is to determine the impact on financial results of liquidity ratios, solvency ratios, and operation ratios as calculated by roe in manufacturing sub-sector food and beverage companies listed on the IDX 20I7-2019. Both financial reports in the fringe and liquor sub-sector were for the population in this study, while the sample in this study was financial reports in the form of a balance sheet and spiritual profits for 3 years (2017-2019). The data collection methodology used in this analysis is recorded by the collection of data or documents collected by accessing the website of the Indonesian Stock Exchange (www.icx.co.id). The results of this study show that the liquidity y ratio variable (X I) partially does not have a substantial impact on financial results (Y) with a significant value of 0,869> 0,05. With a significant value of 0.6 I 7 > 0.05, the solvency ratio variable (X2) has no significant impact on financial results. With a significant value of 0.423> 0.05, the activity ratio variable does not have any significant impact on financial results